2021
DOI: 10.3389/fimmu.2020.619189
|View full text |Cite
|
Sign up to set email alerts
|

The Immune System Can Hear Noise

Abstract: As a stressor widely existing in daily life, noise can cause great alterations to the immune system and result in many physical and mental disorders, including noise-induced deafness, sleep disorders, cardiovascular diseases, endocrine diseases and other problems. The immune system plays a major role in maintaining homeostasis by recognizing and removing harmful substances in the body. Many studies have shown that noise may play vital roles in the occurrence and development of some immune diseases. In humans, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0
2

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 49 publications
1
16
0
2
Order By: Relevance
“…Another mechanism suggested by Prasher is that noise is a stressor itself. Noise alters the self-regulating process of our biological system to keep the stability of one’s body through disruption of the endocrine and immune system [ 70 , 71 , 72 ]. Previous studies have reported that noise-induced stress exposed to both acute and chronic noise increases the cortisol level or disrupts the regulatory mechanism of the cortisol by affecting the HPA function.…”
Section: Discussionmentioning
confidence: 99%
“…Another mechanism suggested by Prasher is that noise is a stressor itself. Noise alters the self-regulating process of our biological system to keep the stability of one’s body through disruption of the endocrine and immune system [ 70 , 71 , 72 ]. Previous studies have reported that noise-induced stress exposed to both acute and chronic noise increases the cortisol level or disrupts the regulatory mechanism of the cortisol by affecting the HPA function.…”
Section: Discussionmentioning
confidence: 99%
“…Noise is one of the most harmful pollutants and common physical factors generated in both living and workplace environments (Dobie, 2017). Noise may lead to not only physical disorders, such as NIHL, but also to mental damage, which may cause more depression, thereby indirectly exerting adverse effects related to other immune-related diseases such as some autoimmune diseases and non-Hodgkin lymphoma (Zhang et al, 2021). Although the direct relationship between noise and the immune system is unclear, a few studies have recently shown that noise can cause some changes in the immune system (Abouee-Mehrizi et al, 2020), including proliferation of immune cells, secretion of cytokines, production of antibodies, and regulation of immunotoxicity (Kim et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…A lo largo de los últimos años, diferentes artículos de revisión con un grandísimo impacto han ido ahondando en estas tesis, completándolas y contrastándolas con más investigaciones (Chanda y Levitin, 2013;De Witte et al, 2019;Fancourt et al, 2013;Revista de Investigación en Musicoterapia, 6, 2022, pp. 19-45. https://doi.org/10.15366/rim2022.6.002 Finn y Fancourt, 2018;Zhang et al, 2021). Es cierto que el cortisol ha sido uno de los biomarcadores del estrés más estudiados, pero también se ha investigado el efecto de la música sobre otras hormonas y neurotransmisores implicados en la psiconeuroinmunología del estrés: epinefrina, norepinefrina, ACTH, DHEA (Finn y Fancourt, 2018).…”
Section: Tablaunclassified
“…Como apuntaba Conrad (2010), este eje neuroendocrino tan importante se desregula con la entrada de inputs estresantes, ocasionando una sobreestimulación que ocasiona una hiperactividad. Según Zhang et al (2021) la música tiene la capacidad de regular la función del sistema inmune, precisamente porque atenúa, apacigua la hiperactividad del eje HPA.…”
Section: Tablaunclassified